Acid-promoted reaction of N-(cyanomethyl) amide with nitrosation reagent: Facile synthesis of 1, 2, 4-oxadiazole-3-carboxamide. (20th July 2021) - Du, Shaoqing; Li, Jin; Fu, Wen; Xu, Xiaoyong; Shao, Xusheng; Qian, Xuhong
Graphical abstract: Highlights: High yield. The yield of the reaction can reach 92%. Room temperature (25 °C) response. Fast response and Simple ingredients. Abstract: 1, 2, 4-Oxadiazole-3-carboxamide has been extensively used in the pharmaceutical chemistry. In this study, 1, 2, 4-oxadiazole-3-carboxamide is accomplished through an acid-promoted reaction of N -(cyanomethyl)amide with nitrosation reagent. This novel preparation of 1, 2, 4-oxadiazole-3-carboxamide was carried out at 25 °C, and the yield of target compounds was as high as 92%. At the same time, the amount of acid used is reduced. A mechanism speculation for the formation of 1, 2, 4-oxadiazole-3-carboxamide has been provided. The new synthetic method provides great convenience for the synthesis of compounds containing 1, 2, 4-oxadiazole-3-carboxamide.